Presión espiratoria positiva para aclaramiento mucociliar en fibrosis quística - Jhoselin Alexandra, Rodríguez Quimbiulco (2021)
ABSTRACT This research work was developed with the modality of bibliographic review, with the aim of compiling information about the efficacy of Positive Expiratory Pressure for mucociliary clearance in patients with cystic fibrosis, in several repositories worldwide that have the required scientific validity. Since cystic fibrosis is a genetic condition that occurs because of abnormalities in the function of the transmembrane regulatory protein of cystic fibrosis, within the mucus-producing cells of the body, a dysfunction that complicates the transport of water and charged ions through the cell membrane resulting in the production of thick and sticky mucus, in the same way it affects several organs and systems of the body. In general, respiratory therapy is mainly used, and it involves a number of techniques that set the objective of clearing the respiratory tract, but of all of them it is necessary to fix the concentration in the therapy with positive expiratory pressure, since these devices allow air to flow freely when inhaling, but not when exhaling, causing the exhalation to be stronger against resistance. 128 worldwide papers were analyzed, then they were thoroughly analyzed with the PEDro scale, of which 35 articles met the criteria for research. The databases that provided the largest number of scientific articles were Pubmed, Scopus and Cochrane. At the end of this investigation, the results obtained were that respiratory therapy with expiratory pressure in patients with cystic fibrosis is totally efficient for mucociliary clearance. Keywords: cystic fibrosis, respiratory tract clearance, mucociliary clearance, positive expiratory pressure